Protective effects of ebselen on sodium-selenite-induced experimental cataract in rats - Aydemir, Orhan; Guler, Mete; Kaya, Mehmet Kaan; Deniz, Nurettin; Ustundag, Bilal (Elsevier Science Inc, 2012)
PURPOSE: To determine whether ebselen has a protective effect or antioxidative potential in a sodium-selenite-induced experimental cataract model. SETTING: Firat University, Elazig, Turkey. DESIGN: Experimental study. METHODS: Twenty-one Sprague-Dawley rat pups were randomly divided into a control group, a sodium-selenite-induced-cataract group, and an ebselen-treated group; each group contained 7 rat pups. Rats in the control group received dimethyl sulfoxide (DMSO) intraperitoneally only and rats in the sodium-selenite-induced-cataract group received 30 nmol/g body weight sodium selenite subcutaneously and DMSO intraperitoneally 10 days postpartum. Rats in the ebselen group received 30 nmol/g body weight sodium selenite subcutaneously 10 days postpartum and were treated with 5 mg/kg body weight ebselen once a day for 4 consecutive days. Cataract development was assessed weekly for 3 weeks by slitlamp examination and graded using a scale. Reduced glutathione (GSH), total nitrite, and malondialdehyde (MDA) levels in lens supernatants were measured at the end of 3 weeks. RESULTS: In the control group, all lenses were clear. In the ebselen-treated group, the mean cataract stage was significantly lower than in the sodium-selenite-induced-cataract group (P = .022). The GSH levels were significantly lower in the sodium-selenite-induced-cataract group than in the control and ebselen groups (P < .001). The MDA levels were lower in the ebselen group than in the sodium-selenite-induced-cataract group (P < .001). The mean total nitrite level was significantly lower in the sodium-selenite-induced-cataract group than in the ebselen group (P = .001). CONCLUSIONS: Ebselen had a protective effect on cataract development in a sodium-selenite-induced experimental model. The protective effect of ebselen appears to be due to inhibition of oxidative stress.
Keywords: Nitric-Oxide; Ischemia/Reperfusion Injury; Lipid-Peroxidation; Oxidative Stress; Lens; Antioxidant; Inhibition; Prevention; Damage; Model